Tunnel-layered composite sodium ion battery positive electrode material and preparation method thereof

CN119447277APending Publication Date: 2025-02-14LIAOCHENG UNIV

Patent Information

Application Number
CN202411521783.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing sodium ion battery positive electrode materials have problems such as low charge and discharge capacity and poor cycle life. The charge and discharge capacity of tunnel oxides is low, and manganese elements in the layered oxide structure are prone to distortion reactions, resulting in manganese dissolution.

Method used

Through heteroatom doping, transition metal oxide micro-nano structure is regulated, transition metal oxide with a tunnel-layer composite phase structure is constructed, and the preparation of the positive electrode material is achieved by co-precipitation technology and high-temperature heat treatment.

Benefits of technology

The capacity and cyclic stability of the positive electrode material are improved, the active site of manganese-based oxide sodium storage is increased, the sodium ion migration and transportation path is broadened, and the energy density and rate performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447277A_ABST
    Figure CN119447277A_ABST
Patent Text Reader

Abstract

The invention relates to the field of preparation of sodium ion battery positive electrode materials, and particularly discloses a tunnel-layered composite sodium ion battery positive electrode material and a preparation method thereof. The molecular formula of the positive electrode material is NaxMn1-yZyO2, Z is any one of copper (Cu) and tungsten (W) elements, x is greater than or equal to 0.44 and less than or equal to 0.9, 0lt; and y < = 0.7. The transition metal oxide with a tunnel-layered composite phase structure is constructed by regulating and controlling the micro-nano structure of the transition metal oxide through heteroatom doping, so that the transition metal oxide sodium ion battery positive electrode material with high charge-discharge capacity, excellent rate capability and long cycle life is realized; the method has an important promotion effect on rapid commercialization of the transition metal oxide positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of preparation of cathode materials for sodium-ion batteries, and particularly to a tunnel-layered composite cathode material for sodium-ion batteries and a preparation method thereof. Background Art

[0002] Disclosing the information of this background art section is only intended to enhance the overall understanding of the present invention, and it is not necessarily regarded as an admission or an implication in any form that this information constitutes the prior art already known to those of ordinary skill in the art.

[0003] Sodium-ion batteries have the advantages of rich raw material sources, low price, high safety, and a wide working temperature range, and have received extensive research and attention from researchers. The rapid development of sodium-ion battery materials also contributes to the further promotion of the rapid development of clean energy to a certain extent, providing important support for the "carbon neutrality" and "carbon peak" goals proposed by China.

[0004] The cathode materials for sodium-ion batteries mainly include transition metal oxides, Prussian blue compounds, organic compounds, polyanion compounds, etc. Among them, transition metal oxides include tunnel-type oxides and layered oxides. Tunnel-type transition metal oxides have the advantages of excellent structural stability and fast sodium-ion migration channels, but they have the problem of low charge-discharge capacity; layered transition metal oxides have high charge-discharge capacity and energy density, but manganese elements in their structures are prone to disproportionation reactions, resulting in manganese dissolution and ultimately poor cycle life. Summary of the Invention

[0005] In view of the above problems, the present invention provides a tunnel-layered composite cathode material for sodium-ion batteries and a preparation method thereof. The present invention regulates the micro-nano structure of transition metal oxides by heteroatom doping to construct a transition metal oxide with a tunnel-layered composite phase structure, and simultaneously improves the capacity and cycle stability of the transition metal oxide. Specifically, the technical solution of the present invention is as follows.

[0006] First, the present invention provides a tunnel-layered composite cathode material for sodium-ion batteries, and its molecular formula is Na x Mn 1-y Z y O2, where Z is any one of copper (Cu) and tungsten (W) elements, 0.44 ≤ x ≤ 0.9, 0 < y ≤ 0.7. Therefore, the cathode material with this structure has a unique tunnel-layered composite phase structure, and the battery prepared by using it has the characteristics of high energy density, high rate performance, and long cycle life.

[0007] Secondly, the present invention discloses a preparation method of the tunnel-layered composite cathode material for sodium-ion batteries, including the following steps: (1) According to the Na x Mn 1-y Z y The atomic ratio of Na, Mn and Z elements in O2 is obtained by weighing the sodium source, manganese source and Z source. Then, each raw material is dissolved in an acidic solution and stirred for reaction, and the coprecipitated compound formed is separated, dried and ground to obtain a precursor for later use.

[0008] (2) Sintering the precursor in an oxygen-containing atmosphere, and then cooling the precursor to obtain the positive electrode material.

[0009] Furthermore, in step (1), the sodium source includes at least one of sodium carbonate, sodium acetate, sodium nitrate, sodium acetate, sodium citrate, etc.

[0010] Furthermore, in step (1), 5-10% of the mass of the sodium source is added to prevent the loss of the sodium source due to volatilization during the high-temperature sintering process.

[0011] Furthermore, in step (1), the manganese source includes at least one of manganese oxalate, manganese sulfate, manganese acetate, manganese nitrate, manganese acetate, etc.

[0012] Furthermore, in step (1), the Z element includes sodium tungstate, copper acetate, etc.

[0013] Furthermore, in step (1), the acidic solution comprises at least one of acetic acid and oxalic acid. Optionally, the concentration of the acidic solution is 1-5 mol / L, and the ratio of each raw material to the acidic solution is 1 g: 10-30 mL.

[0014] Furthermore, in step (1), the stirring reaction temperature is 50-80° C., and the reaction time is 4-6 hours. Optionally, the stirring rate is 120-500 rpm / min.

[0015] Furthermore, in step (1), the drying temperature is 100-120° C. and the drying time is 8-12 hours.

[0016] Furthermore, in step (1), the grinding speed is 200-450 rpm / min, the time is 0.2-2 h, and the ball-to-material ratio is 13-26:1.

[0017] Furthermore, in step (2), the sintering treatment temperature is 700-1000°C and the time is 1-15h. Optionally, the oxygen-containing atmosphere includes air, etc. The present invention adopts a coprecipitation technology method to achieve uniform distribution of each element in the precursor and uniform distribution of the precursor particle size, and realizes rapid preparation of a positive electrode material with a tunnel-layered composite phase structure through a one-step high-temperature heat treatment process. The product component uniformity is good, which greatly saves material preparation time and is convenient for mass production.

[0018] Furthermore, in step (2), the cooling rate is 0.5-15°C / min.

[0019] Compared with the prior art, the present invention has the following beneficial technical effects: the present invention adopts liquid phase coprecipitation method to achieve uniform mixing of element levels between sodium, manganese, oxygen and heteroatoms, and achieves uniform distribution of precursor particle size; after a step of high temperature treatment, a manganese-based positive electrode material with a microscopic morphology of rod-shaped and sheet-shaped mixed is obtained, wherein the introduction of Z element significantly increases the average valence state of manganese in the positive electrode material, thereby improving the structural stability of the material and constructing a tunnel-layered composite phase structure. It is precisely because of this structure that the manganese-based oxide sodium storage active sites are increased and the sodium ion migration and transport paths are broadened, and finally the charging and discharging capacity, energy density and cycle stability of manganese-based sodium ion batteries are significantly improved simultaneously. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. The embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein: Figure 1 The following are X-ray diffractometer spectra (XRD) of tunnel-layered composite manganese-based positive electrode materials prepared in Example 2, Example 4, Example 5, Example 10, Example 11 and Example 12.

[0021] Figure 2 The following are scanning electron microscope (SEM) and transmission electron microscope (TEM) images of the tunnel-layered composite manganese-based positive electrode materials prepared in Example 2, Example 4, Example 5 and Example 12.

[0022] Figure 3 The following is an X-ray electron spectrum (XPS) of the tunnel-layered composite manganese-based positive electrode material prepared in Example 2 and Example 12.

[0023] Figure 4 The following is a charge and discharge curve diagram of the tunnel-layered composite manganese-based positive electrode material prepared in Example 2 and Example 12 at 0.1C.

[0024] Figure 5 The following is a cyclic voltammetry curve of the tunnel-layered composite manganese-based positive electrode material prepared in Example 2 and Example 12 at 0.2 mV / s.

[0025] Figure 6 The following is a rate performance diagram of the tunnel-layered composite manganese-based positive electrode material prepared in Example 2 and Example 12 at different current densities.

[0026] Figure 7 The following is a graph of the long cycle performance of the tunnel-layered composite manganese-based positive electrode material prepared in Example 2 and Example 12 at 2C.

[0027] Figure 8 This is the long cycle performance diagram of the sodium ion full battery constructed with the following Example 2 and hard carbon negative electrode material at 1C. DETAILED DESCRIPTION

[0028] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0029] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. If not otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar to or equivalent to the described content can be applied to the method of the present invention. Now, the present invention is further described in conjunction with the accompanying drawings and specific embodiments of the present invention, and the preferred implementation methods and materials described in the present invention are only for demonstration purposes.

[0030] Example 1 A method for preparing a tunnel-layered composite sodium ion battery positive electrode material comprises the following steps: (1) According to the stoichiometric ratio of sodium source, manganese source and tungsten source = 0.44:0.995:0.005, weigh 1.9122 g of sodium acetate (6% excess), 11.6418 g of manganese acetate and 0.0734 g of sodium tungstate respectively, add them slowly to 15 mL of 2 mol / L acetic acid solution, place them in a magnetic stirrer, stir them thoroughly at a speed of 300 rap / min for 5 h, and the stirring temperature is 60°C.

[0031] (2) The solid-liquid mixture obtained in step (1) was separated by vacuum filtration, and the obtained solid was placed in a forced air drying oven and dried at 100° C. for 12 h. The obtained dry sample was ground by ball milling (ball-to-material ratio of 20:1, ball milling speed of 300 rpm / min) for 0.5 h to obtain a uniform precursor.

[0032] (3) The precursor powder was placed in a corundum crucible, transferred to a muffle furnace, and heated to 900°C at a heating rate of 5°C / min in an air atmosphere and kept at that temperature for 6 h, and then cooled to room temperature at a cooling rate of 15°C / min to obtain tungsten-doped tunnel-layered two-phase manganese-based oxide Na 0.44 Mn 0.995 W 0.005 O2.

[0033] Example 2 A method for preparing a tunnel-layered composite sodium ion battery positive electrode material comprises the following steps: (1) According to the stoichiometric ratio of sodium source, manganese source and tungsten source = 0.44:0.99:0.01, weigh 1.9122 g of sodium acetate (6% excess), 12.0707 g of manganese acetate and 0.2204 g of sodium tungstate respectively, add them slowly to 15 mL of 2 mol / L acetic acid solution, place them in a magnetic stirrer, stir them thoroughly at a speed of 300 rap / min for 5 h, and the stirring temperature is 60°C.

[0034] (2) The solid-liquid mixture obtained in step (1) was separated by vacuum filtration, and the obtained solid was placed in a forced air drying oven and dried at 100° C. for 12 h. The obtained dry sample was ground by ball milling (ball-to-material ratio of 20:1, ball milling speed of 300 rpm / min) for 0.5 h to obtain a uniform precursor.

[0035] (3) The precursor powder was placed in a corundum crucible, transferred to a muffle furnace, and heated to 900°C at a heating rate of 5°C / min in an air atmosphere and kept at that temperature for 6 h, and then cooled to room temperature at a cooling rate of 15°C / min to obtain tungsten-doped tunnel-layered two-phase manganese-based oxide Na 0.44 Mn 0.99 W 0.01 O2.

[0036] Example 3 A method for preparing a tunnel-layered composite sodium ion battery positive electrode material comprises the following steps: (1) According to the stoichiometric ratio of sodium source, manganese source and tungsten source = 0.44:0.985:0.015, weigh 1.9122 g of sodium acetate (6% excess), 12.0707 g of manganese acetate and 0.2204 g of sodium tungstate respectively, add them slowly to 15 mL of 2 mol / L acetic acid solution, place them in a magnetic stirrer, stir them thoroughly at a speed of 300 rap / min for 5 h, and the stirring temperature is 60°C.

[0037] (2) The solid-liquid mixture obtained in step (1) was separated by vacuum filtration, and the obtained solid was placed in a forced air drying oven and dried at 100° C. for 12 h. The obtained dry sample was ground by ball milling (ball-to-material ratio of 20:1, ball milling speed of 300 rpm / min) for 0.5 h to obtain a uniform precursor.

[0038] (3) The precursor powder was placed in a corundum crucible, transferred to a muffle furnace, and heated to 900°C at a heating rate of 5°C / min in an air atmosphere and kept at that temperature for 6 h, and then cooled to room temperature at a cooling rate of 15°C / min to obtain tungsten-doped tunnel-layered two-phase manganese-based oxide Na 0.44 Mn 0.985 W 0.015 O2.

[0039] Example 4 A method for preparing a tunnel-layered composite sodium ion battery positive electrode material comprises the following steps: (1) According to the stoichiometric ratio of sodium source, manganese source and tungsten source = 0.44:0.98:0.02, weigh 1.9122 g of sodium acetate (6% excess), 12.0094 g of manganese acetate and 0.2938 g of sodium tungstate respectively, add them slowly to 15 mL of 2 mol / L acetic acid solution, place them in a magnetic stirrer, stir them thoroughly at a speed of 300 rap / min for 5 h, and the stirring temperature is 60°C.

[0040] (2) The solid-liquid mixture obtained in step (1) was separated by vacuum filtration, and the obtained solid was placed in a forced air drying oven and dried at 100° C. for 12 h. The obtained dry sample was ground by ball milling (ball-to-material ratio of 20:1, ball milling speed of 300 rpm / min) for 0.5 h to obtain a uniform precursor.

[0041] (3) The precursor powder was placed in a corundum crucible, transferred to a muffle furnace, and heated to 900°C at a heating rate of 5°C / min in an air atmosphere and kept at that temperature for 6 h, and then cooled to room temperature at a cooling rate of 15°C / min to obtain tungsten-doped tunnel-layered two-phase manganese-based oxide Na 0.44 Mn 0.98 W 0.02 O2.

[0042] Example 5 A method for preparing a tunnel-layered composite sodium ion battery positive electrode material comprises the following steps: (1) According to the stoichiometric ratio of sodium source, manganese source and tungsten source = 0.44:0.99:0.01, weigh 1.9122 g of sodium acetate (6% excess), 12.0707 g of manganese acetate and 0.2204 g of sodium tungstate respectively, add them slowly to 15 mL of 2 mol / L acetic acid solution, place them in a magnetic stirrer, stir them thoroughly at a speed of 300 rap / min for 5 h, and the stirring temperature is 60°C.

[0043] (2) The solid-liquid mixture obtained in step (1) was separated by vacuum filtration, and the obtained solid was placed in a forced air drying oven and dried at 100° C. for 12 h. The obtained dry sample was ground by ball milling (ball-to-material ratio of 20:1, ball milling speed of 300 rpm / min) for 0.5 h to obtain a uniform precursor.

[0044] (3) The precursor powder was placed in a corundum crucible, transferred to a muffle furnace, and heated to 700°C at a heating rate of 5°C / min in an air atmosphere and kept at that temperature for 6 h, and then cooled to room temperature at a cooling rate of 15°C / min to obtain tungsten-doped tunnel-layered two-phase manganese-based oxide Na 0.44 Mn 0.99 W 0.01 O2-7006.

[0045] Example 6 A method for preparing a tunnel-layered composite sodium ion battery positive electrode material comprises the following steps: (1) According to the stoichiometric ratio of sodium source, manganese source and tungsten source = 0.44:0.99:0.01, weigh 1.9122 g of sodium acetate (6% excess), 12.0707 g of manganese acetate and 0.2204 g of sodium tungstate respectively, add them slowly to 15 mL of 2 mol / L acetic acid solution, place them in a magnetic stirrer, stir them thoroughly at a speed of 300 rap / min for 5 h, and the stirring temperature is 60°C.

[0046] (2) The solid-liquid mixture obtained in step (1) was separated by vacuum filtration, and the obtained solid was placed in a forced air drying oven and dried at 100° C. for 12 h. The obtained dry sample was ground by ball milling (ball-to-material ratio of 20:1, ball milling speed of 300 rpm / min) for 0.5 h to obtain a uniform precursor.

[0047] (3) The precursor powder was placed in a corundum crucible, transferred to a muffle furnace, and heated to 800°C at a heating rate of 5°C / min in an air atmosphere and kept at that temperature for 6 h, and then cooled to room temperature at a cooling rate of 15°C / min to obtain tungsten-doped tunnel-layered two-phase manganese-based oxide Na 0.44 Mn 0.99 W 0.01 O2-8006.

[0048] Example 7 A method for preparing a tunnel-layered composite sodium ion battery positive electrode material comprises the following steps: (1) According to the stoichiometric ratio of sodium source, manganese source and tungsten source = 0.44:0.99:0.01, weigh 1.9122 g of sodium acetate (6% excess), 12.0707 g of manganese acetate and 0.2204 g of sodium tungstate respectively, add them slowly to 15 mL of 2 mol / L acetic acid solution, place them in a magnetic stirrer, stir them thoroughly at a speed of 300 rap / min for 5 h, and the stirring temperature is 60°C.

[0049] (2) The solid-liquid mixture obtained in step (1) was separated by vacuum filtration, and the obtained solid was placed in a forced air drying oven and dried at 100° C. for 12 h. The obtained dry sample was ground by ball milling (ball-to-material ratio of 20:1, ball milling speed of 300 rpm / min) for 0.5 h to obtain a uniform precursor.

[0050] (3) The precursor powder was placed in a corundum crucible, transferred to a muffle furnace, and heated to 1000°C at a heating rate of 5°C / min in an air atmosphere and kept at that temperature for 6 h, and then cooled to room temperature at a cooling rate of 15°C / min to obtain tungsten-doped tunnel-layered two-phase manganese-based oxide Na 0.44 Mn 0.99 W 0.01 O2-10006.

[0051] Example 8 A method for preparing a tunnel-layered composite sodium ion battery positive electrode material comprises the following steps: (1) According to the stoichiometric ratio of sodium source, manganese source and tungsten source = 0.44:0.99:0.01, weigh 1.9122 g of sodium acetate (6% excess), 12.0707 g of manganese acetate and 0.2204 g of sodium tungstate respectively, add them slowly to 15 mL of 2 mol / L acetic acid solution, place them in a magnetic stirrer, stir them thoroughly at a speed of 300 rap / min for 5 h, and the stirring temperature is 60°C.

[0052] (2) The solid-liquid mixture obtained in step (1) was separated by vacuum filtration, and the obtained solid was placed in a forced air drying oven and dried at 100° C. for 12 h. The obtained dry sample was ground by ball milling (ball-to-material ratio of 20:1, ball milling speed of 300 rpm / min) for 0.5 h to obtain a uniform precursor.

[0053] (3) The precursor powder was placed in a corundum crucible, transferred to a muffle furnace, and heated to 900°C at a heating rate of 5°C / min in an air atmosphere and kept at that temperature for 3 h, and then cooled to room temperature at a cooling rate of 15°C / min to obtain tungsten-doped tunnel-layered two-phase manganese-based oxide Na 0.44 Mn 0.99 W 0.01 O2-9003.

[0054] Example 9 A method for preparing a tunnel-layered composite sodium ion battery positive electrode material comprises the following steps: (1) According to the stoichiometric ratio of sodium source, manganese source and tungsten source = 0.44:0.99:0.01, weigh 1.9122 g of sodium acetate (6% excess), 12.0707 g of manganese acetate and 0.2204 g of sodium tungstate respectively, add them slowly to 15 mL of 2 mol / L acetic acid solution, place them in a magnetic stirrer, stir them thoroughly at a speed of 300 rap / min for 5 h, and the stirring temperature is 60°C.

[0055] (2) The solid-liquid mixture obtained in step (1) was separated by vacuum filtration, and the obtained solid was placed in a forced air drying oven and dried at 100° C. for 12 h. The obtained dry sample was ground by ball milling (ball-to-material ratio of 20:1, ball milling speed of 300 rpm / min) for 0.5 h to obtain a uniform precursor.

[0056] (3) The precursor powder was placed in a corundum crucible, transferred to a muffle furnace, and heated to 900°C at a heating rate of 5°C / min in an air atmosphere and kept at that temperature for 9 h, and then cooled to room temperature at a cooling rate of 15°C / min to obtain tungsten-doped tunnel-layered two-phase manganese-based oxide Na 0.44 Mn 0.99 W 0.01 O2-9009.

[0057] Example 10 A method for preparing a tunnel-layered composite sodium ion battery positive electrode material comprises the following steps: (1) According to the stoichiometric ratio of sodium source, manganese source and tungsten source = 0.44:0.99:0.01, weigh 1.9122 g of sodium acetate (6% excess), 12.0707 g of manganese acetate and 0.2204 g of sodium tungstate respectively, add them slowly to 15 mL of 2 mol / L acetic acid solution, place them in a magnetic stirrer, stir them thoroughly at a speed of 300 rap / min for 5 h, and the stirring temperature is 60°C.

[0058] (2) The solid-liquid mixture obtained in step (1) was separated by vacuum filtration, and the obtained solid was placed in a forced air drying oven and dried at 100° C. for 12 h. The obtained dry sample was ground by ball milling (ball-to-material ratio of 20:1, ball milling speed of 300 rpm / min) for 0.5 h to obtain a uniform precursor.

[0059] (3) The precursor powder was placed in a corundum crucible, transferred to a muffle furnace, and heated to 900°C at a heating rate of 5°C / min in an air atmosphere and kept at that temperature for 12 h, and then cooled to room temperature at a cooling rate of 15°C / min to obtain tungsten-doped tunnel-layered two-phase manganese-based oxide Na 0.44 Mn 0.99 W 0.01 O2-90012.

[0060] Embodiment 11 A method for preparing a tunnel-layered composite sodium ion battery positive electrode material comprises the following steps: (1) According to the stoichiometric ratio of sodium source, manganese source and tungsten source = 0.44:0.99:0.01, weigh 1.9122 g of sodium acetate (6% excess), 12.0707 g of manganese acetate and 0.2204 g of sodium tungstate respectively, add them slowly to 15 mL of 2 mol / L acetic acid solution, place them in a magnetic stirrer, stir them thoroughly at a speed of 300 rap / min for 5 h, and the stirring temperature is 60°C.

[0061] (2) The solid-liquid mixture obtained in step (1) was separated by vacuum filtration, and the obtained solid was placed in a forced air drying oven and dried at 100° C. for 12 h. The obtained dry sample was ground by ball milling (ball-to-material ratio of 20:1, ball milling speed of 300 rpm / min) for 0.5 h to obtain a uniform precursor.

[0062] (3) The precursor powder was placed in a corundum crucible, transferred to a muffle furnace, and heated to 900°C at a heating rate of 5°C / min in an air atmosphere and kept at that temperature for 15 h, and then cooled to room temperature at a cooling rate of 15°C / min to obtain tungsten-doped tunnel-layered two-phase manganese-based oxide Na 0.44 Mn 0.99 W 0.01 O2-90015.

[0063] Example 12 A method for preparing a tunnel-type sodium ion battery positive electrode material comprises the following steps: (1) According to the stoichiometric ratio of sodium source to manganese source = 0.44:1, weigh 1.9122 g of sodium acetate (6% excess) and 12.2545 g of manganese acetate, respectively, and slowly add them into 15 mL of 2 mol / L acetic acid solution. Place them in a magnetic stirrer and stir them thoroughly at a speed of 300 rap / min for 5 h. The stirring temperature is 60 °C.

[0064] (2) The solid-liquid mixture obtained in step (1) was separated by vacuum filtration, and the obtained solid was placed in a forced air drying oven and dried at 100° C. for 12 h. The obtained dry sample was ground by ball milling (ball-to-material ratio of 20:1, ball milling speed of 300 rpm / min) for 0.5 h to obtain a uniform precursor.

[0065] (3) The precursor powder was placed in a corundum crucible, transferred to a muffle furnace, and heated to 900°C at a heating rate of 5°C / min in an air atmosphere and kept at that temperature for 6 h, and then cooled to room temperature at a cooling rate of 15°C / min to obtain a tunnel-type manganese-based oxide Na 0.44 MnO2.

[0066] Example 13 A method for preparing a tunnel-layered composite sodium ion battery positive electrode material comprises the following steps: (1) According to the stoichiometric ratio of sodium source, manganese source and tungsten source = 0.44:0.99:0.01, weigh 1.9844 g of sodium acetate (10% excess sodium), 12.1320 g of manganese acetate and 0.1469 g of sodium tungstate respectively, add them slowly to 15 mL of 2 mol / L acetic acid solution, place them in a magnetic stirrer, stir them thoroughly at a speed of 300 rap / min for 5 h, and the stirring temperature is 60°C.

[0067] (2) The solid-liquid mixture obtained in step (1) was separated by vacuum filtration, and the obtained solid was placed in a forced air drying oven and dried at 100° C. for 12 h. The obtained dry sample was ground by ball milling (ball-to-material ratio of 20:1, ball milling speed of 300 rpm / min) for 0.5 h to obtain a uniform precursor.

[0068] (3) The precursor powder was placed in a corundum crucible, transferred to a muffle furnace, and heated to 900°C at a heating rate of 5°C / min in an air atmosphere and kept at that temperature for 6 h, and then cooled to room temperature at a cooling rate of 15°C / min to obtain tungsten-doped tunnel-layered two-phase manganese-based oxide Na 0.44 Mn 0.99 W0.01 O2.

[0069] Embodiment 14 A method for preparing a tunnel-layered composite sodium ion battery positive electrode material comprises the following steps: (1) According to the stoichiometric ratio of sodium source, manganese source and tungsten source = 0.44:0.99:0.01, weigh 1.8942 g of sodium acetate (5% excess), 12.0707 g of manganese acetate and 0.2204 g of sodium tungstate respectively, add them slowly to 15 mL of 2 mol / L acetic acid solution, place them in a magnetic stirrer, stir them thoroughly at a speed of 300 rap / min for 5 h, and the stirring temperature is 60°C.

[0070] (2) The solid-liquid mixture obtained in step (1) was separated by vacuum filtration, and the obtained solid was placed in a forced air drying oven and dried at 100° C. for 12 h. The obtained dry sample was ground by ball milling (ball-to-material ratio of 20:1, ball milling speed of 300 rpm / min) for 0.5 h to obtain a uniform precursor.

[0071] (3) The precursor powder was placed in a corundum crucible, transferred to a muffle furnace, and heated to 900°C at a heating rate of 5°C / min in an air atmosphere and kept at that temperature for 6 h, and then cooled to room temperature at a cooling rate of 15°C / min to obtain tungsten-doped tunnel-layered two-phase manganese-based oxide Na 0.44 Mn 0.99 W 0.01 O2.

[0072] Embodiment 15 A method for preparing a tunnel-layered composite sodium ion battery positive electrode material comprises the following steps: (1) According to the stoichiometric ratio of sodium source, manganese source, and copper source = 0.44:0.99:0.01, weigh 1.9122 g of sodium acetate (6% excess), 12.1320 g of manganese acetate, and 0.0998 g of copper acetate, respectively, and slowly add them to 15 mL of 2 mol / L acetic acid solution in sequence. Place them in a magnetic stirrer and stir them thoroughly at a speed of 300 rap / min for 5 h. The stirring temperature is 60°C.

[0073] (2) The solid-liquid mixture obtained in step (1) was separated by vacuum filtration, and the obtained solid was placed in a forced air drying oven and dried at 100° C. for 12 h. The obtained dry sample was ground by ball milling (ball-to-material ratio of 20:1, ball milling speed of 300 rpm / min) for 0.5 h to obtain a uniform precursor.

[0074] (3) The precursor powder was placed in a corundum crucible, transferred to a muffle furnace, and heated to 900°C at a heating rate of 5°C / min in an air atmosphere and kept at that temperature for 6 h, and then cooled to room temperature at a cooling rate of 15°C / min to obtain tungsten-doped tunnel-layered two-phase manganese-based oxide Na 0.44 Mn 0.99 Cu 0.01 O2.

[0075] Example 16 A method for preparing a tunnel-layered composite sodium ion battery positive electrode material comprises the following steps: (1) According to the stoichiometric ratio of sodium source, manganese source and tungsten source = 0.9:0.99:0.01, weigh 3.9114 g of sodium acetate (6% excess), 12.0707 g of manganese acetate and 0.2204 g of sodium tungstate respectively, add them slowly to 15 mL of 2 mol / L acetic acid solution, place them in a magnetic stirrer, stir them thoroughly at a speed of 300 rap / min for 5 h, and the stirring temperature is 60°C.

[0076] (2) The solid-liquid mixture obtained in step (1) was separated by vacuum filtration, and the obtained solid was placed in a forced air drying oven and dried at 100° C. for 12 h. The obtained dry sample was ground by ball milling (ball-to-material ratio of 20:1, ball milling speed of 300 rpm / min) for 0.5 h to obtain a uniform precursor.

[0077] (3) The precursor powder was placed in a corundum crucible, transferred to a muffle furnace, and heated to 900°C at a heating rate of 5°C / min in an air atmosphere and kept at that temperature for 6 h, and then cooled to room temperature at a cooling rate of 15°C / min to obtain tungsten-doped tunnel-layered two-phase manganese-based oxide Na 0.9 Mn 0.99 W 0.01 O2.

[0078] Embodiment 17 A method for preparing a tunnel-layered composite sodium ion battery positive electrode material comprises the following steps: (1) According to the stoichiometric ratio of sodium source, manganese source and tungsten source = 0.44:0.93:0.07, weigh 1.9122 g of sodium acetate (6% excess), 11.3967 g of manganese acetate and 1.0284 g of sodium tungstate respectively, add them slowly to 15 mL of 2 mol / L acetic acid solution, place them in a magnetic stirrer, stir them thoroughly at a speed of 300 rap / min for 5 h, and the stirring temperature is 60°C.

[0079] (2) The solid-liquid mixture obtained in step (1) was separated by vacuum filtration, and the obtained solid was placed in a forced air drying oven and dried at 100° C. for 12 h. The obtained dry sample was ground by ball milling (ball-to-material ratio of 20:1, ball milling speed of 300 rpm / min) for 0.5 h to obtain a uniform precursor.

[0080] (3) The precursor powder was placed in a corundum crucible, transferred to a muffle furnace, and heated to 900°C at a heating rate of 5°C / min in an air atmosphere and kept at that temperature for 6 h, and then cooled to room temperature at a cooling rate of 15°C / min to obtain tungsten-doped tunnel-layered two-phase manganese-based oxide Na 0.44 Mn 0.93 W 0.07 O2.

[0081] Embodiment 18 A method for preparing a tunnel-layered composite sodium ion battery positive electrode material comprises the following steps: (1) According to the stoichiometric ratio of sodium source, manganese source and tungsten source = 0.44:0.99:0.01, weigh 1.9122 g of sodium acetate (6% excess), 12.0707 g of manganese acetate and 0.2204 g of sodium tungstate respectively, add them slowly to 15 mL of 2 mol / L acetic acid solution, place them in a magnetic stirrer, stir them thoroughly at a speed of 300 rap / min for 5 h, and the stirring temperature is 60°C.

[0082] (2) The solid-liquid mixture obtained in step (1) was separated by vacuum filtration, and the obtained solid was placed in a forced air drying oven and dried at 100° C. for 12 h. The obtained dry sample was ground by ball milling (ball-to-material ratio of 20:1, ball milling speed of 300 rpm / min) for 0.5 h to obtain a uniform precursor.

[0083] (3) The precursor powder was placed in a corundum crucible, transferred to a muffle furnace, and heated to 900°C at a heating rate of 5°C / min in an air atmosphere and kept at that temperature for 1 h, and then cooled to room temperature at a cooling rate of 15°C / min to obtain tungsten-doped tunnel-layered two-phase manganese-based oxide Na 0.44 Mn 0.99 W 0.01 O2.

[0084] Performance Test: (1) Assembly of button sodium ion half-cell: Weigh 0.08 g of the positive electrode material in the above Examples 1 to 18, 0.01 g of the conductive agent Super P, and 0.01 g of the binder polyvinylidene fluoride (the mass ratio of the three materials is 80:10:10), and evenly disperse them in 2 mL of N-methylpyrrolidone. Stir well to form an electrode slurry, and evenly coat the slurry on an aluminum foil. Place the electrode piece in a vacuum drying oven at 100°C for 12 h, and cut it into a circular positive electrode piece with a diameter of 12 mm by a roller machine and a slicer. In an inert gas glove box (H2O≤0.01ppm, O2≤0.01ppm), a metal sodium sheet with a diameter of 14mm and a thickness of 0.2mm was used as the negative electrode, a 12mm circular electrode sheet was used as the positive electrode, Whatman's GF / F was used as the separator, and 1mol / L sodium perchlorate was dissolved in ethylene carbonate and propylene carbonate (volume ratio 1:1, containing 5% fluoroethylene carbonate) as the electrolyte to assemble a CR2032 button half-cell. For the charge and discharge test of the above button half-cell, the test voltage range was 2~4V, and the current density was 1C=120mA / g.

[0085] (2) Assembly of button sodium ion full battery: Weigh 0.08g of Kuraray hard carbon (Type 2), conductive agent Super P0.01g, binder sodium hydroxymethyl cellulose 0.01g (the mass ratio of the three materials is 80:10:10), the above materials are evenly dispersed in 2mL deionized water to form an electrode slurry, which is evenly coated on an aluminum foil, and the electrode piece is placed in a vacuum drying oven at 100°C for 12h. After being rolled by a roller machine, it is cut into a circular negative electrode piece with a diameter of 12mm by a slicer. In an inert gas glove box (H2O≤0.01ppm, O2≤0.01ppm), the above circular electrode piece is used as the negative electrode piece, the circular electrode piece prepared by the above (1) is used as the positive electrode piece, Whatman's GF / F is used as a separator, and 1mol / L sodium perchlorate is dissolved in ethylene carbonate and propylene carbonate (volume ratio 1:1, containing 5% fluoroethylene carbonate) as an electrolyte to assemble into a CR2032 button-type sodium ion full battery. For the above button full battery charge and discharge test, the test voltage range is 1.5~4V, and the current density is 1C=120mA / g.

[0086] The test results are analyzed as follows: Figure 1 1 is the X-ray diffraction pattern of the above-mentioned embodiment 2, embodiment 4, embodiment 5, embodiment 10, embodiment 11 and embodiment 12. As can be seen from the figure, the peak position of the diffraction peak of embodiment 12 is similar to that of the tunnel-type transition metal oxide Na 0.44 The diffraction peak positions of MnO2 (PDF No. 27-0750) are basically consistent, all belonging to the orthorhombic system and Pbam space group, and there are few impurities in the samples. The diffraction peak positions of Example 2, Example 4, Example 5, Example 10 and Example 11 are consistent with those of the tunnel transition metal oxide Na0.44 MnO2 and layered transition metal oxides Na 0.91 MnO2 (PDF No.38-0692) and Na 0.7 MnO 2.05 The diffraction peak position of (PDF No.27-0751) corresponds to that of the prepared manganese-based oxide positive electrode material, which indicates that there are two phase structures of tunnel type and layered type in its structure.

[0087] Figure 2 The micromorphology SEM and TEM images of Example 2, Example 4, Example 5 and Example 12 are shown. As can be seen from the figure, the micromorphology of Example 12 presents a typical rod-like structure, with a length of about 6 to 10 μm, a width of about 3 to 6 μm, and a uniform particle size distribution. In addition, it can be seen from the SEM images of Example 2, Example 4 and Example 5 that the microstructure is composed of a rod-like and a sheet-like two-phase structure, and it can be seen from the TEM image that the sheet-like structure presents a more obvious polygonal structure, which further illustrates that the prepared manganese-based oxide positive electrode material is mainly composed of a tunnel-type and layered structure.

[0088] Figure 3 The XPS graphs of Example 2 and Example 12 show that the ratio of trivalent manganese to tetravalent manganese in the positive electrode material increases from 82% in Example 12 to 87% in Example 2, which indicates that the average valence state of manganese is significantly increased, which helps to improve the structural stability of the electrode material and ultimately improve the cycle stability of the material.

[0089] Figure 4 The charge / discharge curves of the sodium ion half-cells constructed in Example 2 and Example 12 at 0.1C, and the charge / discharge specific capacities thereof are 157.3 / 153.1 mAh g −1 and 120.1 / 118.3mAh g −1 .

[0090] Figure 5 The cyclic voltammograms of the sodium ion half-cells constructed in Examples 2 and 12 at 0.2 mV / s show that Example 12 presents six pairs of obvious redox peaks, which is consistent with the sodium ion storage mechanism during the charge and discharge process of the tunnel-type manganese-based oxide. In addition, the redox peak of Example 2 is relatively broad, which is caused by the embedding / de-embedding of sodium ions in the layered oxide material during the charge and discharge process.

[0091] Figure 6The rate performance test diagram of the sodium ion half-cell constructed in Example 2 and Example 12 shows that the average charge / discharge specific capacities at 0.1, 0.2, 0.5, 1, 2 and 5C are 152.6 / 150.7, 130.2 / 128.7, 114.8 / 113.9, 104.9 / 103.9, 99.4 / 97.9, 92.3 / 92.1 mAh g −1 and 118.7 / 117.9, 106.5 / 106.2, 97.5 / 97.2, 94.1 / 93.7, 90.1 / 89.2 and 84.6 / 84.6 mAh g −1 , and the coulombic efficiency of the sodium ion half-cells assembled in Example 2 and Example 12 can reach 100%.

[0092] Figure 7 The long cycle performance test diagram of the sodium ion half-cell constructed in Example 2 and Example 12 at 2C shows that after 300 cycles, the capacity retention rates of Example 2 and Example 12 are 77% and 57%, respectively, proving that the positive electrode material prepared in Example 2 significantly improves the long cycle stability of the battery.

[0093] Figure 8 The long cycle performance diagram of the sodium ion full battery assembled with the hard carbon negative electrode material in Example 2 at 1C shows that the initial charge / discharge specific capacity of the sodium ion full battery constructed in Example 2 is 84.9 / 84.8 mAh / g at 1C. After 300 cycles, the charge / discharge specific capacity is 55.6 and 55.4 mAh / g, the capacity retention rate is 66%, and the coulombic efficiency is 100%. This shows that the tunnel-layered mixed phase manganese-based sodium ion battery positive electrode material prepared in Example 2 has high capacity and long cycle stability.

[0094] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A tunnel-layered composite sodium ion battery positive electrode material, characterized in that: The molecular formula of the positive electrode material is Na x Mn 1-y Z y O2, where Z is any one of copper and tungsten, 0.44≤x≤0.9, 0 <y≤0.7。 2. The method for preparing the tunnel-layered composite sodium ion battery positive electrode material according to claim 1, characterized in that: The steps include: (1) According to the Na x Mn 1-y Z y The atomic ratio of Na, Mn and Z elements in O2 is as follows: weigh the sodium source, manganese source and Z source; then dissolve each raw material in an acidic solution and react with stirring, separate the formed coprecipitated compound, dry it and grind it to obtain a precursor for later use; (2) Sintering the precursor in an oxygen-containing atmosphere, and then cooling the precursor to obtain the positive electrode material.

3. The method for preparing the tunnel-layered composite sodium ion battery positive electrode material according to claim 2, characterized in that: In step (1), the sodium source includes at least one of sodium carbonate, sodium acetate, sodium nitrate, sodium acetate, and sodium citrate.

4. The method for preparing the tunnel-layered composite sodium ion battery positive electrode material according to claim 2, characterized in that: In step (1), 5-10% of the mass of the sodium source is added.

5. The method for preparing the tunnel-layered composite sodium ion battery positive electrode material according to claim 2, characterized in that: In step (1), the manganese source includes at least one of manganese oxalate, manganese sulfate, manganese acetate, manganese nitrate and manganese acetate.

6. The method for preparing the tunnel-layered composite sodium ion battery positive electrode material according to claim 2, characterized in that: In step (1), the Z element includes sodium tungstate and copper acetate.

7. The method for preparing the tunnel-layered composite sodium ion battery positive electrode material according to claim 2, characterized in that: In step (1), the acidic solution includes at least one of acetic acid and oxalic acid; Optionally, in step (1), the concentration of the acidic solution is 1-5 mol / L; Optionally, in step (1), the ratio of each raw material to the acidic solution is 1 g: 10-30 mL.

8. The method for preparing the tunnel-layered composite sodium ion battery positive electrode material according to claim 2, characterized in that: In step (1), the stirring reaction temperature is 50-80°C and the reaction time is 4-6 hours; Optionally, in step (1), the stirring rate is 120-500 rpm / min; Optionally, in step (1), the drying temperature is 100-120° C. and the drying time is 8-12 hours.

9. The method for preparing a tunnel-layered composite sodium ion battery positive electrode material according to any one of claims 2 to 8, characterized in that: In step (1), the grinding speed is 200-450 rpm / min, the time is 0.2-2 h, and the ball-to-material ratio is 13-26:

1.

10. The method for preparing a tunnel-layered composite sodium ion battery positive electrode material according to any one of claims 2 to 8, characterized in that: In step (2), the sintering treatment is carried out at a temperature of 700-1000°C and a time of 1-15 hours; Optionally, in step (2), the oxygen-containing atmosphere includes air; Optionally, in step (2), the cooling rate is 0.5-15°C / min.

Citation Information

Patent Citations

  • Preparation method of sodium ion battery layered and tunnel composite structure manganese-based anode material

    CN105118984A

  • Sodium ion battery positive electrode material, preparation method thereof and sodium ion battery comprising same

    CN109607624A

  • Layered-tunnel composite material and phase proportion regulation method thereof

    CN109860576A

  • High-specific-capacity sodium ion battery positive electrode material, preparation method thereof and sodium ion battery

    CN115692708A

Cited By

  • High-sodium-content tunnel type oxide positive electrode material, preparation method, sodium ion battery positive electrode and sodium ion battery

    CN119841355A

  • A high sodium content tunnel-type oxide positive electrode material, preparation method, sodium ion battery positive electrode and sodium ion battery

    CN119841355B